Changes in Some Chemical and Physical Properties of a Sandy Clay Loam Soil During the Decomposition of Hazelnut Husk - CANDEMIR, FERIDE; GULSER, COSKUN (Asian Journal of Chemistry, 2010)
Hazelnut husk was applied at the rates of 0 (control), 2, 4 and 6 % to a sandy clay loam soil in order to investigate effect of hazelnut husk on some chemical and physical soil properties during its mineralization period for 16 weeks. Experiment was conducted at 4 different incubation periods (1, 4, 8 and 16 weeks) under the same laboratory conditions. Hazelnut husk treatments increased organic carbon content, electrical conductivity, aggregate stability, volumetric water content, total porosity and lowered bulk density of the soil over the control treatment. During the 16 weeks incubation period, organic carbon content for hazelnut husk treatments decreased while the electrical conductivity values of the soil increased. Organic carbon content gave a significant negative relationship (-0.984**) with electrical conductivity value. Mean bulk density of the soil significantly decreased from 1.25 g cm-3 for control to 1.05 g cm-3 for 6 % hazelnut husk treatment. Increases in the mean porosity and the mean volumetric water content for 6 % hazelnut husk rate over the control were 14.3 and 26.2 %, respectively. The highest aggregate stability was determined with 6 % of hazelnut husk application rate in the eight week. Aggregation in soils slowed down after eight weeks and disaggregation occurred for all application rates in the last incubation period due to possibility of more substrate demands of bacteria and bacterial attack on products which bind soil particles together.